EXPLORATION AND UTILIZATION OF LOCAL BIODIVERSITY WITH THE POTENTIAL FOR EMPOWERMENT OF CONSERVATION VILLAGE MODELS FATUSENE VILLAGE, NORTH CENTRAL TIMOR SUBDISTRICT - Remigius Binsasi; Polikarpia Wilhelmina Bani (Media Konservasi, 2021)
Biodiversity is a strategic resource and plays a role in determining the quality of human life. This study aimed to determine the types of vegetation that were used and developed for the empowerment of conservation village model, know the local potential that could be empowered to develop conservation village models, analyze community empowerment activities related to the use of local biodiversity, and analyze factors related to the utilization of local biodiversity that had the potential to empower the people of Fatusene Village. The techniques used in data collection were survey, interview, and documentation. The approach used was qualitative and quantitative descriptive. The results showed that there were 17 tree species from 11 families found in several springs in the Fatusene Village area. The plant species that had the highest and lowest importance value index were Zyzygium aqueum and Leucaena leucocephala with an importance Value Index of 47.28% and 5.45%, respectively. The distribution of plant species was not evenly distributed at each spring point, indicating the influence of abiotic environmental factors and human activities that greatly affected the existence of plants in terms of conservation. Local potentials that could be empowered and utilized to develop a conservation village model in the Fatusene Village area were agriculture and plantations, livestock, and forestry. The community empowerment activities in Fatusene Village are usually held before the implementation of activities within one year to discuss village community empowerment programs and other unexpected events such as crop failure, problems with clean water, environmental sanitation and other physical developments. To support this activity, it is carried out reforestation around the springs, reducing tree exploitation which is one of the contributions to water availability, protecting and preserving springs as a source of life for the people of Fatusene Village, East Miomaffo District, North Central Timor Regency. Key words: Conservation Village Model, Exploration, Fatusene Local Biodiversity